Prednisone‐free maintenance immunosuppression in obese kidney transplant recipients. Issue 10 (7th August 2019) - Matas, Arthur J.; Vock, David M.
Abstract: Obese transplant recipients (BMI ≥ 30 kg/m 2 ) have decreased posttransplant patient and graft survival compared with their nonobese counterparts. At the same time, many prednisone‐related side effects (eg, new‐onset diabetes) are similar to those associated with obesity. Using SRTR data, we studied outcomes associated with prednisone‐free maintenance immunosuppression (rapid discontinuation of prednisone—RDP). Between January 1, 2000, and December 31, 2014, 44 635 first transplant recipients with BMI ≥ 30 kg/m 2 had a first kidney transplant (28 176 DD; 16 459, LD); 12, 994 (29%) were discharged from the hospital on a prednisone‐free protocol. We compared outcomes to those discharged on a protocol incorporating maintenance prednisone (intention‐to‐treat analysis). RDP‐treated obese first DD recipients had significantly better patient survival (HR, 0.88; CI, 0.81‐0.96) and graft survival (HR, 0.93; CI, 0.88‐0.99) compared with their counterparts on maintenance immunosuppression. Although not statistically significant, the same trends were seen for LD recipients. For both DD and LD recipients, there was no difference between groups for death‐censored graft survival, suggesting that the benefit of RDP was due to improved patient survival. Our findings suggest that kidney transplant recipients with BMI ≥ 30 kg/m 2 benefit from a protocol that incorporates RDP.